2001
DOI: 10.1017/s0033291701003725
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and environmental influences on anorexia nervosa syndromes in a population–based twin sample

Abstract: Findings support previous research indicating significant genetic and non-shared environmental influences on AN syndromes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
137
3
3

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(155 citation statements)
references
References 11 publications
(20 reference statements)
5
137
3
3
Order By: Relevance
“…The overall heritability of AN was moderate, and lower than that obtained in both the only previous study to examine the full AN diagnosis , as well as that found in studies using broader definitions of AN (e.g., Klump et al, 2001;Kortegaard et al, 2001;Wade et al, 2000). However, the current estimate is within the (albeit wide) CI obtained in the Bulik et al study.…”
Section: Discussioncontrasting
confidence: 74%
See 2 more Smart Citations
“…The overall heritability of AN was moderate, and lower than that obtained in both the only previous study to examine the full AN diagnosis , as well as that found in studies using broader definitions of AN (e.g., Klump et al, 2001;Kortegaard et al, 2001;Wade et al, 2000). However, the current estimate is within the (albeit wide) CI obtained in the Bulik et al study.…”
Section: Discussioncontrasting
confidence: 74%
“…Thus, the relatively higher influence of E found in the current study, compared to others which have evaluated AN at the diagnostic level (e.g., Bulik et al, 2006;Klump et al, 2001;Kortegaard et al, 2001;Wade et al, 2000) could reflect both measurement error and nonshared environmental experiences. It is not possible to determine exactly what proportion of variance accounted for by E in this study is due to either true unshared experiences or to measurement error.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…24,25 Genetic epidemiological studies have documented the familiality of AN (relative risk 11.3 in first-degree relatives of AN probands) 26,27 and the estimated twin-based heritability of AN ranges from 33 to 84%. [28][29][30][31][32] Genome-wide linkage studies did not narrow the genomic search space in a compelling manner. [33][34][35] Findings from candidate gene studies of AN resemble those for most complex biomedical diseases-initial intriguing findings diminished by the absence of rigorous replication.…”
Section: Introductionmentioning
confidence: 99%
“…44,45,[88][89][90][91][92][93] Nonetheless, environment may play an important role in the expression of underlying genetic predispositions. The concept of gene-environment correlation may be highly relevant to understanding how the cycle of risk is perpetuated.…”
Section: Gene-environment Correlationmentioning
confidence: 99%